Role of ICAM-1 in the aggregation and adhesion of human alveolar macrophages in response to TNF-α and INF-γ - Masahiro Sasaki; Yuriko Namioka; Takefumi Ito; Noriko Izumiyama; Shin Fukui; Akiko Watanabe; Masayuki Kashima; Masaaki Sano; Takanobu Shioya; Mamoru Miura (Hindawi Limited, 2001)
Intracellular adhesion molecule-1 (ICAM-1)-mediated cell-cell adhesion is thought to play an important role at sites of inflammation. Recent evidence suggests that ICAM-1 surface expression on alveolar macrophages is increased in pulmonary sarcoidosis and that inflammatory granuloma formation is characterized by the aggregation of macrophages. The present study shows that ICAM-1 expression is significantly elevated on alveolar macrophages from patients with sarcoidosis in response to tumor necrosis factor-α (TNF-α) and interferon- γ (INF-γ) compared with healthy controls. Aggregation and adhesion were significantly increased in alveolar macrophages treated with TNF-α and INF-γ, and significantly inhibited in those pretreated with a monoclonal antibody to ICAM-1. Similarly, aggregation and adhesion were inhibited in macrophages treated with heparin, which then exhibited a wide range of biological activities relevant to inflammation. These results suggested that the surface expression of ICAM-1 on alveolar macrophages in response to TNF-α and INF-γ is important in mediating aggregation and adhesion. Additionally, heparin may be useful for developing novel therapeutic agents for fibrotic lung disease.